2018
DOI: 10.5863/1551-6776-23.5.390
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Induces Migrating Motor Complexes in Pediatric Patients Undergoing Antroduodenal Motility Studies

Abstract: OBJECTIVE Erythromycin (ERY) is used in the treatment of gastroparesis; however, this medication is associated with serious side effects, such as cardiac arrhythmias and consequent cardiorespiratory arrest. Azithromycin (AZM) has been suggested as an alternative to ERY as a result of its improved safety profile. Intravenous ERY (1 mg/kg) is administered during antroduodenal motility studies to induce migrating motor complexes (MMCs), the presence or absence of which helps diagnose motility disorders like gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Like ERY, AZM can bind to the motilin receptor, resulting in a concentration-dependent increase in intracellular calcium and stimulation of cholinergic mediated smooth muscle contractions in adults to a level comparable to ERY (11,22,23); however, AZM and ERY have different pharmacodynamic and pharmacokinetic profiles, resulting in non-equivalent recommended dosing (24,25). AZM has a large volume of distribution (23 L/kg) and low peak serum level (0.4 mg/mL), demonstrating extensive tissue distribution and intracellular accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like ERY, AZM can bind to the motilin receptor, resulting in a concentration-dependent increase in intracellular calcium and stimulation of cholinergic mediated smooth muscle contractions in adults to a level comparable to ERY (11,22,23); however, AZM and ERY have different pharmacodynamic and pharmacokinetic profiles, resulting in non-equivalent recommended dosing (24,25). AZM has a large volume of distribution (23 L/kg) and low peak serum level (0.4 mg/mL), demonstrating extensive tissue distribution and intracellular accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…There is data in adults comparing the use of AZM with ERY during antroduodenal manometry (7). To date, published studies that examine the effectiveness of AZM as an alternative to ERY for prokinetic therapy in children are scarce and have examined only small numbers of patients (11). Due to an interruption in the supply of intravenous ERY, we were forced to turn to AZM as an alternative to ERY for pediatric ADM.…”
Section: What Is Newmentioning
confidence: 99%
See 1 more Smart Citation
“…We used intravenous azithromycin in our protocol due to the shortage of erythromycin during the study period. Azithromycin has also been used as a provocative agent during ADM study and shown to have similar effects as erythromycin (22–24). Our data revealed fewer phase III MMC induced by azithromycin compared to the previously reported.…”
Section: Discussionmentioning
confidence: 99%